Correlation of the job turnover intention of Iranian nurses with job satisfaction and burnout in the COVID-19 pandemic - Maede Fasih Far; Hamid Sharif Nia; Abdolghader Assarroudi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The COVID-19 pandemic has led to numerous psychological consequences and a drastic increase in the workload of nurses. The present study aimed to investigate the correlation of the job turnover intention of Iranian nurses with job satisfaction and burnout in the COVID-19 pandemic. MATERIALS AND METHODS: This cross-sectional descriptive study was conducted on 300 nurses working in the hospitals in Sabzevar, Iran from October 2020 to January 2021. Data were collected using the questionnaires of turnover intention, Spector job satisfaction, and Maslach burnout in a self-report manner. Correlation analysis was used. Then, for assessing a predictive model used a simple linear regression and multiple linear regression analyses. Data analysis was performed using SPSS version 24. RESULTS: The results showed that the variables of burnout and job satisfaction are effective on nurses' willingness to job turnover. Furthermore, among the background variable, the findings showed that the economic status of nurses and the male gender of patients under their care can be effective on nurses "job turnover intention and can be used as predictor variables of nurses" job turnover intention. CONCLUSION: According to the results, special attention must be paid to the job satisfaction, burnout, and the economic situation (as a mediator variable) of nurses to prevent their job turnover in the COVID-19 pandemic. Therefore, it is recommended that health managers prevent the job turnover intention of nurses in the COVID-19 pandemic by taking psycho-socio-economic support measures.